Experimental study on the movement characteristics of pedestrians under sudden contact forces. (30th June 2021) - Li, Xudong; Xu, Xuan; Zhang, Jun; Jiang, Kechun; Liu, Weisong; Yi, Ruolong; Song, Weiguo
Abstract: In crowd disasters, collision among pedestrians is one of the main causes of crushing and trampling. However, in most controlled experiments, there is little physical contact among pedestrians, and microscopic human behaviors are less studied. Therefore, a series of controlled experiments where physical contact occurred were conducted to study the microscopic dynamics of a single pedestrian's movement process and the transmission of impulse between two pedestrians. The impulse can be extracted from a flexible fabric pressure sensor that covers the pedestrian's back. In the single-pedestrian experiment, the body postures and behaviors are analyzed. It is found that the impulse release distance increases as the impulse increases and the numerical linear relation is established to show the trend. The polynomial relation in the movement process is adopted and the numerical relations between speed, move distance and exerted impulse are established. In the two-pedestrian experiment, the transmission of impulse is studied. The transmission coefficient increases first and then decreases as the distance increases and the numerical rational relation is adopted to show the trend. The transmitted impulse increases as the exerted impulse increases in each distance and the numerical exponential relation is adopted. These equations can be used to study the impulse transmitted along the queue. The findings in this study can help us to understand pedestrian collision evacuation dynamics in a high-density crowd. Eventually, they could be used to assess the risk levels in local crowds and prevent crowd disasters involving trampling.